Register Variation in European Football Commentary: A Study of Language Use in Live Sports Broadcasting - Djamereng, Jumharia; Abdullah, Muhammad Ali Emir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Register variation, a central concept in sociolinguistics, refers to how language adapts to specific social and situational contexts. This study investigates register as it operates in live European football commentary, a high-intensity communicative environment where language must perform multiple simultaneous functions. Drawing on register theory, the research employs a descriptive qualitative method to analyze transcribed commentary from major football matches broadcast on official platforms. The data were coded and interpreted using a framework focused on lexical choice, syntactic structure, tonal modulation, and rhythmic delivery. The findings reveal that football commentators employ a fluid, adaptive register marked by idiomatic expressions, clause fragmentation, evaluative and rhetorical tone, and dynamic pacing. These features serve both narrative and affective purposes, enhancing audience engagement and constructing shared emotional experiences. The study contributes to sociolinguistic theory by situating register within live, performative media discourse, offering insights into how language functions as social action in real-time contexts. The implications extend to sports media, discourse analysis, and broader media linguistics, where understanding register can inform training, content design, and cross-cultural communication strategies.